Student#x2019;s Intention to Conduct Research Studies: The Case Study of Final Year Undergraduates in the Department of Finance, University of Sri Jayewardenepura, Sri Lanka (Global Journal of Management and Business Research, 2019)
This research attempts to answer the question #x201C;Do undergraduates have an intention to do research?#x201D; The study took place at the Department of Finance, Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, Sri Lanka, and the respondents are the final year undergraduate of the department. Following theoretical findings of Sachithra (2015), and Pacifica and Thomson (2011), the study looked at the attitudes of students in doing research within the degree program and the gender differences in the preference for doing research. The quantitative approach is the methodology adopted and used a questionnaire as the data collection tool, and it consists of both open and close-ended questions. Percentage analysis and coding are the main analytical tools used for analyzing data, and supplemented by graphs, charts, and tables. Findings reveal that students#x2019; attitudes have a significant impact on their intention to do research. Further, gender difference too affects whether students intend to do research. In conclusion, it can be stated that the male students have a higher preference to do research than female students and the intention to do research varies with the degree program the students follow along with their preferred job in the future.
Keywords: intention to do research; student attitudes; gender difference; undergraduates in finance